Improving Water Productivity Helps Provide Food Security in Drylands - Nangia, Vinay; Yadava, Narendra Dev (Annals of Arid Zone, 2016)
The article discusses background of water use in agriculture in the dry areas; the past, present and future projections of water scarcity in the dry regions. It highlights some of the latest debates, principles and terminologies used in the field of agricultural water management. And, finally discusses an ongoing project in the Indira Gandhi Nahar Pariyojana where these principles are being applied to improve the field- and irrigation scheme-scale water productivity of the farming systems.